CHILDHOOD TRAUMA AND FEAR OF INTIMACY IN UNIVERSITY STUDENTS: EXPLORING THE MEDIATING ROLE OF ATTACHMENT STYLE AND THE MODERATING INFLUENCE OF PERCEIVED SOCIAL SUPPORT (Contemporary Journal of Social Science Review, 2025)
This study investigated the relationship between childhood trauma and fear of intimacy, with perceived social support as a potential moderator and attachment style as a potential mediator. Data was taken from 202 university students. Data was collected through self-reported questionnaires, including the Childhood Trauma Questionnaire - Short Form, Adult Attachment Questionnaire, Multidimensional Scale of Perceived Social Support, and Fear of Intimacy Scale. Results showed that childhood trauma significantly predicted fear of intimacy, with sexual abuse as a key predictor. Avoidant attachment significantly mediated the relationship between childhood trauma and fear of intimacy, particularly when perceived social support was low. Lower perceived social support amplified the effect of childhood trauma on avoidant attachment. The findings show the impact of childhood trauma on adult intimacy, emphasizing the protective role of social support and the mediating role of avoidant attachment. Key implications include the need for trauma-informed interventions focusing on attachment patterns, the importance of creating supportive connections and forming culturally sensitive approaches regarding family dynamics in Pakistan.